Dust Aerosol Vertical Profiles in the Hinterland of Taklimakan Desert During Summer 2019 - Bi, Jianrong; Li, Zhengpeng; Zuo, Dapeng; Yang, Fan; Li, Bowen; Ma, Junyang; Huang, Zhongwei; He, Qing (Frontiers in Environmental Science, 2022)
The dust aerosol vertical profiles are very essential to accurately evaluate their climate forcing and trans-subcontinental transportation to downstream areas. We initiated a jointly comprehensive field experiment to investigate the vertical profiles and optical characteristics of dust aerosol in the hinterland of Taklimakan Desert (TD) during summer 2019. After smoothing the raw signals, the CHM15k ceilometer could distinctly detect moderate intensity of dust layer, cloud layer, and subsequent rainfall process. The results showed that dust events frequently occurred in TD during the entire period, the overall mean PM2.5, PM10, PM2.5/PM10, and Ångström exponent are 110.4±121.0 g/m3, 317.2±340.0 g/m3, 0.35±0.07, and 0.28±0.12, respectively, suggesting that dust particles are predominant aerosol types in TD. There was an obvious summertime dust stagnation layer persistently hanged over the desert at 1.5-3.0 km height. And a deep and intense daytime convective structure was also detected by ceilometer, with maximum aerosol mixing layer height (AMLH) of ~3 km appeared at 12:00 UTC, which was in favor of lifting the ground-generated dust particles into upper atmosphere. The normalized range-corrected signal log10(RCS), aerosol extinction (z) and backscattering coefficient (z) of ceilometer were higher than 6.2, 0.5 km-1, and 0.01 km-1sr-1 for heavy dust storms, respectively, and the corresponding vertical optical range (VOR) was smaller than 1.0 km, and aerosol lidar ratio was equal to 50 sr, which was greatly different from those of clear sky cases. The retrieved (z) values were about 2.0 km-1, 0.5 km-1, 0.14 km-1, and 0.10 km-1 at 200 m height, respectively, under strong dust storm, blowing dust, floating dust, and clear-sky conditions. This indicated that aerosol extinction coefficients under dust events were about 3~10 times greater than those of clear-sky cases. The statistics of aerosol optical parameters under different dust intensities in TD were very helpful to exploring and validating dust aerosols in the applications of climate models or satellite remote sensing.